2017
DOI: 10.1007/s00520-017-3639-2
|View full text |Cite
|
Sign up to set email alerts
|

Online support groups for young women with breast cancer: a proof-of-concept study

Abstract: This study suggests that therapist-led synchronous OSGs are feasible, acceptable, and useful for young breast cancer survivors and that a future RCT with a larger sample size, perhaps more focused on non-urban areas, is needed to establish its effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…These changes proved to be valuable as our dropout rate reduced substantially by the third cohort. The overall dropout rate was 20%, which is consistent with other online dropout rates in psychooncology …”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These changes proved to be valuable as our dropout rate reduced substantially by the third cohort. The overall dropout rate was 20%, which is consistent with other online dropout rates in psychooncology …”
Section: Discussionsupporting
confidence: 87%
“…The availability of resources required to deliver face‐to‐face services is another challenge. Patients face long waiting lists for treatment when there is a lack of local expert therapists . Such barriers can result in prolonged suffering for patients and highlight the importance of utilizing alternative delivery formats, including online interventions …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various web‐based interventions, such as web‐based collaborative care interventions, online support groups, and computer‐tailored physical activity, have shown positive effects in patients coping with cancer. Previous reviews reported the positive impacts of web‐based interventions in providing support and information for cancer patients or caregivers and in positively influencing caregivers' social and psychological outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…A Cochrane Review of six online support group interventions in women with breast cancer concluded low quality and mixed results provide insufficient evidence supporting their use in this context [95**]. Two single-arm designs [96,97] and three RCTs [98,99,100] reporting psychoeducation, online support groups, supportive-expressive group therapy, or combinations thereof concur.…”
Section: Support Groups Supportive Expressive Therapy and Counsellingmentioning
confidence: 99%